Sistem Terintegrasi untuk Mendeteksi Perubahan Lingkungan dengan Algoritma Frame Difference dan Dynamic - Adaptive Template Matching menggunakan Raspberry Pi dan Virtual Private Network (VPN) - Ardianto Wibowo; Muhammad Ihsan Zul; M Arif Fadly Ridha; M Mahrus Zain (Politeknik Caltex Riau, 2020)
Theft of empty houses and rampant illegal parking is a problem that often occurs in the community, causing anxiety. For this reason, a solution that can provide alarms / notifications automatically if such conditions occur to registered users is needed. This research develops an integrated system that has the ability to detect changes in environmental conditions, such as the occurrence of illegal parking or the presence of strangers in the house, through monitoring of connected IP cameras. The image captured through an IP camera is processed using the Frame Difference algorithm, to further be decided whether it includes an environmental condition changes or not. Compared to conventional IP cameras or IP cameras that include motion detection features, this research system has advantages in terms of notification form flexibility and internet connection flexibility.